Vitalizing Self-Empowerment in Mediating Effect of Good Governance and Workplace Spirituality on Lecturers Organizational Citizenship Behavior at East Java - Ria Mennita; Dita Ika Ayuning Tias (INVENTORY: JURNAL AKUNTANSI, 2023)
The aims of this paper are to determine the mediating role of self-empowerment on the causality relations between good governance and workplace spirituality on Organizational Citizenship Behavior (OCB) among lecturers. There are so many educational-institutions in East Java have developed to survive in competition with fellow universities. In this case the role of the lecturer is needed and highly expected to achieve organizational goals. In this case, OCB has been an important part in organization that means employee willing to do extra role job. The method of this study contains of theoretical direction and quantitative as core method. Structural Equation Modelling analysis is used by using WarpPLS7.0 software. The results show that workplace spirituality and self-empowerment had significant positive effect on OCB, however good governance has no effect. This study also proved that self-empowerment has mediating effect on good governance and workplace spirituality to OCB. This study can be discussed and expanded by researchers and practitioners by adding new variables that relevant to OCB. The main implication of this result is Institutions must be able to optimally provide supports, in the form of facilities and services to employees so that employees feel empowered and support OCB.